Solder Joint Reliability Prediction for Multiple Environments - Perkins, Andrew E.; Sitaraman, Suresh K.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Solder Joint Reliability Prediction for Multiple Environments provides industry engineers, graduate students, academic researchers, and reliability experts with insights and useful tools for evaluating solder joint reliability of ceramic area array electronic packages under multiple environments. The material presented here is not limited to ceramic area array packages only, it can also be used as a methodology for relating numerical simulations and experimental data into an easy-to-use equation that captures the essential information needed to predict solder joint reliability. Such a methodology is often needed to relate complex information in a simple manner to managers and non-experts in solder joint who work with computer server applications as well as for harsh environments such as those found in the defense, space, and automotive industries. Drawing upon years of practical experience and using numerous examples and illustrative applications, Andrew Perkins and Suresh Sitaraman cover state of the art technologies in solder joint reliability, including: A comprehensive summary of current literature on lead-containing ceramic area array electronic package solder joining reliability, Useful and easy-to-use tools for predicting solder joint fatigue life under thermal cycling, and power cycling enviroments, New insight into solder joint reliability testing under multiple environments, including vibration environments, A methodology for predicting solder joint reliability using numerical simulations and experimental data under multiple environments that can be related to any package type. Solder Joint Reliability Prediction for Multiple Environments is a must have book for practitioners and researchers who specialize in solder.
Background -- Literature Review -- Unified Finite Element Modeling for Prediction of Solder Joint Fatigue -- Validation of Unified FEM for Thermal Cycling and Power -- Development of Fatigue Life Equations Under Low-Cycle Thermal and Power Cycling -- Validation of Unified FEM and Development of Fatigue-life Equations for Vibration -- Universal Predictive Fatigue Life Equation and the Effect of Design Parameters -- Acceleration Factor to Relate Thermal Cycles to Power Cycles for CBGA Packages -- Solder Joint Fatigue Failure under Sequential Thermal and Vibration Environments -- Solder Joint Reliability Assessment for Desktop and Space Applications.
Keywords: Engineering; Quality control; Reliability; Industrial safety; Electronics; Microelectronics; Optical materials; Electronic materials; Metals; Engineering; Electronics and Microelectronics, Instrumentation; Metallic Materials; Optical and Electronic Materials; Quality Control, Reliability, Safety and Risk; Electronic books